Faktor-Faktor yang Berkaitan dengan Pemilihan Kontrasepsi IUD - Herni Nursiah; Delvira Andini; Sobar Darmaja (Politeknik Karya Husada, 2025)
Factors Associated with the Choice of IUD Contraception Among Couples of Reproductive Age at the Bdn. Hj. Siti Marpuah, S.Stdi Family Planning Clinic in Cipondoh, Tangerang City, in 2025. The use of long-acting contraceptive methods, particularly the Intrauterine Device (IUD), remains low despite its high effectiveness in reducing birth rates. This study aims to identify factors associated with the selection of IUDs among couples of reproductive age (PUS) at TPMB Bdn. Hj. Siti Marpuah, S.ST in 2025, focusing on knowledge, attitudes, and spousal support. The research method employs a quantitative approach with a cross-sectional design. The population consisted of all PUS who were participants in the family planning (KB) program, with a sample of 80 respondents selected through total sampling. Data were collected using a questionnaire and analyzed univariately and bivariately using the Chi-Square test. The results showed that the majority of respondents were aged 20–35 years (88.8%), had a high school education or equivalent (37.5%), were unemployed (70.0%), were multiparous (63.8%), chose an IUD (98.8%), had good knowledge (95.0%), had a positive attitude (90.0%), and received support from their husbands (97.5%). The Chi-Square test revealed significant associations between knowledge (p=0.000), attitude (p=0.003), and spousal support (p=0.000) and the choice of IUD contraception. In conclusion, knowledge, attitude, and spousal support are significantly associated with the choice of contraception